Pemodelan Bangkitan Perjalanan Pelajar di Kota Pariaman - Sari Andriani; Ilham Mulyawan (Jurnal Ilmiah Rekayasa Sipil, 2020)
Abstract Due to the large number of secondary schools located in Central Pariaman District (Kota Pariaman), this region is attractive to students, both from within and outside the district. The impact received from various transportation problems that arise due to increased traffic flow that occurs by these students. Therefore, this study aims to develop the origin and destination zones of student trips and build a model of trip generation students in Central Pariaman District, both consisting of trip generation models (travel production) and movement pull (travel attraction) using data obtained through household interview survey (home interview survey) in North, and South Pariaman Districts. Trip generation modeling produced in this study is a spatial distribution of traffic generation and movement pull and numerical models generated through data processing with the SPSS program. The independent variable that influences student movement is the population, while the variable that influences the attraction of movement is the number of students.